2018
DOI: 10.1177/1043986217750424
|View full text |Cite
|
Sign up to set email alerts
|

When Bad News Arrives: Project HOPE in a Post-Factual World

Abstract: On the basis of limited empirical evidence, advocates of Project HOPE (Hawaii's Opportunity Probation with Enforcement) have succeeded in spreading the model to a reported 31 states and 160 locations. A recent randomized control experiment across four sites has revealed negative results: no overall effect on recidivism. In this context, we examine how prominent advocates of Project HOPE have coped with the arrival of this "bad news." Despite null findings from a "gold standard" evaluation study, advocates cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The task of encouraging a treatment philosophy has arguably been made even more difficult in recent years with the revival of faith in the power of punishment in the form of community supervision programs like Project HOPE (Hawaii's Opportunity with Probation Enforcement) and swift, certain, and fair (SCF) punishment (Hawken & Kleiman, 2009). These programs have become wildly popular in recent years across the country, spreading to over 160 locations across over 30 states (Cullen, Pratt, Turanovic, & Butler, 2018). And like the conservative-led get-tough approaches of the past, the HOPE/SCF model assumes that a stint of incarceration-what might be termed "jail therapy"-will cure offenders of their criminal ills (Kleiman, 2016).…”
Section: Embrace a Treatment Philosophymentioning
confidence: 99%
See 1 more Smart Citation
“…The task of encouraging a treatment philosophy has arguably been made even more difficult in recent years with the revival of faith in the power of punishment in the form of community supervision programs like Project HOPE (Hawaii's Opportunity with Probation Enforcement) and swift, certain, and fair (SCF) punishment (Hawken & Kleiman, 2009). These programs have become wildly popular in recent years across the country, spreading to over 160 locations across over 30 states (Cullen, Pratt, Turanovic, & Butler, 2018). And like the conservative-led get-tough approaches of the past, the HOPE/SCF model assumes that a stint of incarceration-what might be termed "jail therapy"-will cure offenders of their criminal ills (Kleiman, 2016).…”
Section: Embrace a Treatment Philosophymentioning
confidence: 99%
“…The difference, however, is that HOPE/SCF is the brainchild of liberal scholars and practitioners-a program that was developed and evangelized by those who are more progressive ideologically (Cullen, Manchak, & Duriez, 2014; see also the discussion by Cullen et al, 2018). Thus, as progressive policymakers adopt a liberal version of "punishment works," a key group who may have otherwise been sympathetic to embracing a treatment philosophy might now be harder to convince that it has merit.…”
Section: Embrace a Treatment Philosophymentioning
confidence: 99%
“…Similar to other criminal justice innovations (e.g., boot camps, intensive supervision programs, Project HOPE), problem-solving courts have been adopted widely based on limited empirical evidence (see Cullen & Jonson, 2017;Cullen, Pratt, Turanovic, & Butler, 2018). As a pragmatic enterprise, these courts are driven by local concerns and interestsand not by criminological theory or rigorous research (Boldt, 2014).…”
Section: Courts In Practicementioning
confidence: 99%
“…Last, as boring as it sounds, "treatment as usual" (TAU) poses an extraordinary and unusual array of research and policy challenges that should not be minimized or ignored by the field (Cullen, Pratt, Turanovic, and Butler, 2018). To illustrate, meta-analytic results from the mental health field have demonstrated that the size of a treatment effect is contingent on the control condition, which is often diverse (Washington State Institute for Public Policy, 2017;Watts, Turnell, Kladnitski, Newby, and Andrews, 2015).…”
mentioning
confidence: 99%
“…Although SCF is a hotly debated and polarizing intervention among scholars (Cullen, Pratt, and Turanovic, ; Cullen, Pratt, Turanovic, and Butler, ; Hawken, ; Kleiman, ; Kleiman, Kilmer, and Fisher, ), I read the empirical research base as evidence that reveals both cause for concern as well as for celebration of SCF. Concern clearly emerges from the lack of definitive effectiveness of SCF as implemented among a heterogenous population (Cullen et al., , ; Drake, ) . Additionally, SCF contains programmatic elements that have not been favorably supported by the broader research evidence in community corrections.…”
mentioning
confidence: 99%